Coastal Community Values for Marsh-Dependent Socioecological Services Revealed through a Systematic Qualitative Approach. (7th July 2017) - Wainger, Lisa; McMurray, Anna; Paolisso, Michael; Johnson, Katherine J.; Needelman, Brian
Abstract : A qualitative ranking method, Q methodology, was used to assess stakeholder priorities for socioecological services derived from coastal marshes and communities. The goal was to reveal strength of concerns for and tradeoffs among effects of coastal resilience strategies. Factor analysis identified three perspectives that formed a spectrum from high to low priorities on intangible services. Academic and government stakeholders were more likely than local residents to prioritize intangible services, but stakeholder views were diverse. A collaborative learning process promoted some alignment of views and academics showed the most movement – towards residents' perspectives. Q-sort appeared effective at efficiently synthesizing broad concerns.